International Trade Indicators, 2003: Indonesia - Brotosusilo, Agus (Indonesian Journal of International Law, 2004)
Being obsessed by the desire and willingness to implement liberal economic system for more than thirty years under dictator leaders, the national regulations in Indonesia have led toward the liberalization on trade by its executive and legislative bodies. Those kind of actions are a prove that the government is not aware with the way of living of Indonesian people, which is based on spiritual values. There is a huge gap between the legal system order and regulations with the culture of Indonesian people, and it would lead to the growth of corruption, collusion, and nepotism (KKN) in many sectors of living and endless multidimensional crisis in Indonesia.